Investigation of waste-derived and low-cost calcium oxide-based catalysts in co-pyrolysis of EFB-HDPE to produce high quality bio-oil - Hakim, K.A.K.M.; Tan, E.S.; Habib, S.H.; Hafriz, R.S.R.M.; Salmiaton, A. (Elsevier B.V., 2024)
This study evaluated and compared the bio-oil yield produced from the co-pyrolysis of empty fruit bunch (EFB) and high-density polyethylene (HDPE) feedstock using four calcium oxide (CaO)-based catalysts. Three catalysts were derived from waste sources, namely, clamshell (CS), eggshell (ES), and chicken bone (CB), whereas Malaysia dolomite (MD) was extracted from limestone. Pure CaO catalyst served as a control experiment for comparison purposes. Surface area (BET), particle size (PSA), X-ray diffraction (XRD), and scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM/EDX) examinations were used to compare all catalysts. BET and PSA demonstrated that waste-derived catalysts (CS, CB, ES) have the properties required for co-pyrolysis to produce good yield and quality of bio-oil, whilst XRD and SEM/EDX revealed the existence of CaO compound in each of the catalysts. The co-pyrolysis of EFB-HDPE was performed under controlled conditions in a fluidized-bed reactor. All co-pyrolysis parameters such as catalyst loading, feedstock loading, gas flow, and temperature were fixed for all reactions. The study explored the effect of each catalyst on the catalytic cracking of EFB-HDPE through the bio-oil yield and hydrocarbon composition from the reaction. The chemical composition of the bio-oil samples was analyzed by gas chromatography–mass spectrometry (GC-MS) analysis, whereas the bio-oil yield was calculated using mass-balance equation. The maximum oil yield was 26.07 wt for ES, whereas pure CaO generated a 52.39 hydrocarbon composition, the highest among all catalysts, followed by ES.